Crushing Behavior of Graded Auxetic Structures Built from Inverted Tetrapods under Impact. Issue 1 (12th October 2018) - Novak, Nejc; Borovinšek, Matej; Vesenjak, Matej; Wormser, Maximilian; Körner, Carolin; Tanaka, Shigeru; Hokamoto, Kazuyuki; Ren, Zoran
Abstract : In this study, the crushing behavior of auxetic structures built from inverted tetrapods with linearly graded porosity under impact is analyzed both experimentally and computationally. The auxetic samples with linearly graded porosity are fabricated from Ti‐6Al‐4V alloy powder by the selective electron‐beam melting method. A detailed geometrical analysis of the fabricated samples based on micro computed tomography (microCT) scans is performed to determine the variation of strut thickness and other fabrication imperfections. The samples are subjected to high strain rate compression loading in two specimen orientations (specimens with low or high porosity facing the impacting plate) using the powder gun. Appropriate computational models are later developed and validated to provide a more detailed insight into the crushing mechanism of auxetic structures during impact. The experimental and computational results show dependency of the plateau stress inclination (progressive/regressive) on the gradation of the auxetic cellular structures (specimens with low or high porosity in front). These initial results prove that it is possible to tailor the mechanical behavior of a porous structure with introduction of graded porosity, especially in the case of high strain rate impact, where the main deformation occurs at the impacting front. Abstract : The crushing behavior of auxetic structures built from inverted tetrapods with graded porosity under impact is analyzed experimentally and computationally. The results show dependency of the plateau stress inclination on the gradation of the auxetic cellular structures. These initial results prove that it is possible to tailor the mechanical behavior of a auxetic structure with introduction of graded porosity.